2001
DOI: 10.1016/s0014-5793(01)02871-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Empty’ minicircles and petB/atpA and psbD/psbE (cytb559 α) genes in tandem in Amphidinium carterae plastid DNA1

Abstract: Amphidinium carterae minicircle chloroplast DNA was separated from total DNA by centrifugation through a sucrose/NaCl gradient. Sequences of minicircles with psbA and 23S rRNA contained a common region of 67 bp. Primers designed from this generated numerous polymerase chain reaction products of 1.5^2.6 kb. These contained psaA and psaB as one gene/circle, and petB/atpA and psbD/psbE as two genes/ circle.`Empty' minicircles of 1.7^2.5 kb containing no identifiable genes or parts of genes were more abundant than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 22 publications
1
64
1
Order By: Relevance
“…Uchida (1988) showed that peridinin dinoflagellates have a divergent ferredoxin and later found that dinoflagellate psbA sequences are also extremely divergent from other algae (Takishita and Uchida 1999). Using density gradient centrifugation Zhang (1999) and later Barbrook and Howe (2000) as well as Hiller (2001), and Bachvaroff (unpublished) have separated circular, or plasmid-like DNAs from peridinin dinoflagellates. These minicircles encode one or sometimes two genes, although partial or incomplete genes have also been found (Hiller 2001).…”
Section: Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Uchida (1988) showed that peridinin dinoflagellates have a divergent ferredoxin and later found that dinoflagellate psbA sequences are also extremely divergent from other algae (Takishita and Uchida 1999). Using density gradient centrifugation Zhang (1999) and later Barbrook and Howe (2000) as well as Hiller (2001), and Bachvaroff (unpublished) have separated circular, or plasmid-like DNAs from peridinin dinoflagellates. These minicircles encode one or sometimes two genes, although partial or incomplete genes have also been found (Hiller 2001).…”
Section: Bmentioning
confidence: 99%
“…Using density gradient centrifugation Zhang (1999) and later Barbrook and Howe (2000) as well as Hiller (2001), and Bachvaroff (unpublished) have separated circular, or plasmid-like DNAs from peridinin dinoflagellates. These minicircles encode one or sometimes two genes, although partial or incomplete genes have also been found (Hiller 2001). The messenger RNA for psbA is located in the plastid and therefore it is likely that the minicircles are also in the plastid (Takishita et al 2003).…”
Section: Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Unigenic DNA minicircles of 2-3 kbp that encode plastid gene functions have been found in a number of different peridinin-containing dinoflagellates, including species of Heterocapsa (Zhang et al, 1999(Zhang et al, , 2002, Amphidinium operculatum (Barbrook & Howe, 2000;Barbrook et al, 2001), Amphidinium carterae (Hiller, 2001) and Protoceratium reticulatum (Zhang et al, 2002). The non-coding regions of the minicircles are highly divergent across dinoflagellate genera, except that short stretches of a single nucleotide are frequent.…”
Section: Introductionmentioning
confidence: 99%